Evaluation of Potential Factors affecting the Distribution of Mysids (Crustacea: Mysidacea) in Puttalam Lagoon, Sri Lanka - Nandanie Punchihewa, Neetha (International Journal of Environment, 2020)
Limited information is available on mysids in estuarine systems in Sri Lanka. Present study attempts to find out the distribution of mysids in Puttalam lagoon and also to evaluate the possible factors affecting its distribution. The spatial distributional survey recorded 30 mysid habitats. Mesopodopsis zeylanica, Mesopodopsis orientalis and a new Sirella srilankensis were identified, with M. orientalis being the most abundant and widely distributed species. Survey of temporal variation in mysid abundance was also carried out at two sites for a six months period. This collection of M. orientalis was the first record in Sri Lanka. Distribution of mysid species is primarily dependent on the salinity. Other than the salinity distribution, and abundance of mysids depend on water level and boundary conditions. The occurrence of mysids exhibited a strong positive correlation (P ≤ 0.01) with boundary condition of the lagoon, while presence of garbage, water level, and salinity correlated negatively. Furthermore, species distribution were strongly and positively correlated (P ≤ 0.01) with boundary conditions and negatively correlated with salinity and presence of garbage. The occurrence of M. zeylanica depended on low salinity level while M. orientalis and S. srilankensis depended on high salinity. Lower water levels and boundary vegetation were more favorable for mysids along with sites consisting of mangroves or widespread seagrass beds while soil filled boundary areas and waste disposal sites along the boundary were found to be unsuitable. Reforestation and restoration of mangrove boundary areas can enhance the biodiversity in the lagoon.